Tadeusza Stycznia objawianie osoby - MERECKI, Jarosław (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
The paper seeks to reconstruct the philosophy of the person implied by the ethical writings of Tadeusz Styczeń. In particular the author poses two questions: What is – according to Styczeń – the proper method of philosophical anthropology? and: Which experiences reveal the very essence of the personal being? As far as the method of philosophical anthropology is concerned Styczeń adopted the phenomenological method in its form developed by Karol Wojtyła in his anthropological treatise The Acting Person. According to Styczeń, anthropology should start from the immediate experience of the person and the direct insight into the personal being is accessible first of all in the self−experience of the philosopher. Nevertheless philosophy cannot be practiced as a sort of «egology,» hence the necessity to test the reliability of one’s own experience through the confrontation with the experience of other persons. The next step consists in the interpretation of the material gathered in the phenomenological description, that is from the phenomenology the philosopher passes to the metaphysics of the human person. At the same time, even as a metaphysician the philosopher should always control his theory returning to experience. According to Styczeń, the act of stating the truth is the experience that reveals the essence of the person in the most evident way. In the act of passing the judg− ment on something the person transcends the boundaries of his/her own being and states the truth that does not depend on him/her. At the same time the act of stating the truth implies that the person interiorizes the truth in question and becomes its witness. In this, for Styczeń, anthropology and ethics start from the same original experience and develop its distinct aspects.